Incidence of amyotrophic lateral sclerosis in the United States, 2014–2016. Issue 5 (3rd July 2022) - Mehta, Paul; Raymond, Jaime; Punjani, Reshma; Larson, Theodore; Han, Moon; Bove, Frank; Horton, D. Kevin
Abstract: Objective: To estimate the incidence of amyotrophic lateral sclerosis (ALS) in the United States for calendar years 2014–2016 using data from the National ALS Registry (Registry). The Registry collects data on ALS patients in the United States to better describe the epidemiology of ALS, examine risk factors such as environmental and occupational exposures, and characterize the demographics of those living with the disease. Methods: To identify adult incident cases of ALS, the Registry compiles data from three national administrative databases (maintained by the Centers for Medicare and Medicaid Services, the Veterans Health Administration, and the Veterans Benefits Administration). For cases that are not included in these databases, the Registry includes data collected from patients who voluntarily enroll via a secure web portal. Results: The Registry identified 5695 ALS cases in 2014; 6045 cases in 2015; and 4861 cases in 2016 for age-adjusted incidence rates of 1.7 (2014), 1.5 (2015), and 1.5 (2016) per 100, 000 U.S. population, respectively. ALS was more common among whites, males, and persons aged 60–79 years. Conclusions: This is the first time administrative and self-reported databases have been used to describe the incidence of ALS for the United States resulting in a better estimate of disease demographics.